To Impose or Not Impose Penalty Conditions Following Professional Misconduct: What Factors Are Cited by Three Professional Disciplinary Tribunals in New Zealand? - Lois Surgenor; Kate Diesfeld; Marta Rychert; Olivia Kelly; Kate Kersey (Laws)
Profession-related disciplinary tribunals consider a range of factors when determining penalties following findings of professional misconduct. Penalties that impose conditions on practice hold the potential to facilitate practitioners’ rehabilitation back to safe practice. This study explores the use of penalty conditions by three disciplinary tribunals in New Zealand (the Lawyers and Conveyancers Tribunal [LCDT]; the Health Practitioners Disciplinary Tribunal [HPDT]; and the Teachers Disciplinary Tribunal [TDT]). Disciplinary decisions published between 2018 and 2022 (N = 538) were analysed, coding the explicit reasons cited for imposing or not imposing conditions and if rehabilitation was cited as a penalty principle. Conditions were imposed in 58.6% of the cases, though tribunals varied. All of the tribunals commonly referred to the concepts of remorse/insight, or lack of it, as reasons for ordering or not ordering conditions, and they often considered the seriousness of the misconduct. Reasons for not ordering conditions were more varied between tribunals, as was citing rehabilitation as a penalty principle. The findings suggest that tribunals give substantial consideration to the decision of imposing conditions, drawing on both objective (e.g., past misconduct) and subjective (e.g., cognitive and psychological) phenomena. The reasons did align with concepts found in broad sentencing guidelines from some other jurisdictions (e.g., criminal justice response), though future research on defining and measuring these concepts may help understand their predictive and protective utility.